Seropositivity of dengue cases at a tertiary care centre in Chhindwara, Madhya Pradesh: A three year trend - Purti C. Tripathi; Himanshu Singh; Rahul Kumar Suryawanshi; Ritesh Upadhyay (Infectious Medicine, 2023)
Background: During the recent decades, dengue virus infection has been emerged as a major public health problem. Dengue is one of the important mosquito borne infections causing high mortality and morbidity of humans. Methods: This study was carried out from October 2018 to December 2020. A total of 354 serum samples of clinically suspected dengue patients were tested for immunoglobulin M (IgM) anti-dengue antibodies by dengue monoclonal antibody capture enzyme-linked immunosorbent assay (NIV DEN IgM Capture MAC ELISA). Seasonal variations, age and sex wise incidences were also determined. Results: Total of 354 serum samples were processed from October 2018 to December 2020. Each year males were mostly infected with Dengue 08, 10, and 03 in 2018, 2019, and 2020, respectively. Age group 11–20 was found to be mostly infected by Dengue in case of both male and female. The prevalence of Dengue in each year was from July to November might be due to the rainy season. Clinical characteristics of patients such as fever, headache, abdominal pain and nausea/vomiting, retro-orbital pain, epistaxis, petechiae, altered sensorium, positive tourniquet test were reported. Conclusions: Continuous dengue virus surveillance is required for monitoring of dengue virus so that early detection can be carried out. Effective vector control measures should be implemented for early detection of impending outbreak and to initiate timely control measures.